2020
DOI: 10.3390/biom10050713
|View full text |Cite
|
Sign up to set email alerts
|

Hemistepsin A Inhibits Cell Proliferation and Induces G0/G1-Phase Arrest, Cellular Senescence and Apoptosis Via the AMPK and p53/p21 Signals in Human Hepatocellular Carcinoma

Abstract: Hemistepsin A (HsA), a natural sesquiterpene lactone isolated from Hemistepta lyrata, has been known as a wide range of anti-tumor effects. The aim of this study was to determine whether HsA suppresses hepatocellular carcinoma (HCC) and to figure out the cellular signaling pathways involved in the anti-HCC activities by experiments using the Huh7 cells (a human HCC cell line) and a xenograft HCC model. In this study, HsA completely inhibited HCC cell proliferation, presumably because it induced G0/G1 cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…To ensure the in vivo anti-cancer efficacy of HsA, a further extensive study using various types of human cancer cells using in vivo xenograft model should be performed. Second, like other natural products 41 , HsA might bind to the other molecular targets, such as previously reported Nrf2 and NF-κB in inflammation and hepatic fibrosis 42 , 43 , and AMPK in liver cancer 44 . AMPK could be regulated by Acetyl-CoA or ATP production which is regulated by PDK inhibitors 45 , 46 .…”
Section: Discussionmentioning
confidence: 89%
“…To ensure the in vivo anti-cancer efficacy of HsA, a further extensive study using various types of human cancer cells using in vivo xenograft model should be performed. Second, like other natural products 41 , HsA might bind to the other molecular targets, such as previously reported Nrf2 and NF-κB in inflammation and hepatic fibrosis 42 , 43 , and AMPK in liver cancer 44 . AMPK could be regulated by Acetyl-CoA or ATP production which is regulated by PDK inhibitors 45 , 46 .…”
Section: Discussionmentioning
confidence: 89%
“…The preparation of cell lysates and the process of Western blot analysis were performed as previously described [ 41 , 42 ]. Briefly, harvested cells were lysed in ice-cold radioimmunoprecipitation (RIPA) lysis buffer containing 50 mmol/L Tris–HCl (pH 7.4), 150 mmol/L NaCl, 1% NP-40, 0.1% SDS, 1.0 mmol/L PMSF, 1.0 mmol/L Na 3 VO 4 , and a protease inhibitor tablet (Roche, Indianapolis, IN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that P53 was a major factor in AKI by mediating tubular cell apoptosis ( Ying et al, 2014 ; Chen et al, 2016b ; Tang et al, 2019 ). Previous study indicated that activated AMPK suppresses P53 ( Baek et al, 2020 ), other research demonstrated that compound C suppresses P53 activation through inhibition of AMPK ( Jin et al, 2020 ), while another study suggested that compound C could induce P53 expression, phosphorylation and nuclear translocation of the p53 in cancers ( Huang et al, 2013 ; Zhao et al, 2018 ). The current study has provided in vitro and in vivo evidences for the suppressive effect of compound C on P53.…”
Section: Discussionmentioning
confidence: 99%